2010
DOI: 10.1039/b911040b
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification of stabilisers in polypropylene using time-of-flight mass spectrometry and DART as ion source

Abstract: A method for analysing plastic samples without any sample pretreatment using direct analysis in real time mass spectrometry (DART-MS) was developed. DART-MS allows the direct, simple and rapid identification of polymer additives in plastic products. To demonstrate the suitability of DART-MS for the detection of a wide range of commonly employed stabilising agents, a test set of 21 stabilisers was selected. In a first step standard solutions of these stabilisers in toluene as well as toluene-extracts from polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Considering the performance achieved for most of the compounds, the heater temperature was finally set to 400°C. The influence of flow rate was investigated, since optimizing the helium flow rate promotes the desolvation of analytes and their transportation towards the transfer tube [11,12]. A flow rate of 0.09 m 3 /h gave the best performance for most of phytohormones, except for GA 3 , which preferred a higher flow rate.…”
Section: Optimization Of the Dart-ms Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the performance achieved for most of the compounds, the heater temperature was finally set to 400°C. The influence of flow rate was investigated, since optimizing the helium flow rate promotes the desolvation of analytes and their transportation towards the transfer tube [11,12]. A flow rate of 0.09 m 3 /h gave the best performance for most of phytohormones, except for GA 3 , which preferred a higher flow rate.…”
Section: Optimization Of the Dart-ms Conditionsmentioning
confidence: 99%
“…When DART is coupled to various types of MS, DART-MS provides a rapid and straightforward way to analyze a variety of samples; for example, it has been used for the analysis of pheromones in live Drosophila [9], the quantitation of chemical warfare agents [10], the identification of stabilizers in polypropylene [11], the screening of synthetic drug adulteration [12], and the quantification of small molecules in plasma [13]. During DART-MS analysis, helium (He) or nitrogen (N 2 ) is usually used as the working gas, and excited metastable He or N 2 is generated through a coronato-glow discharge in the DART chamber [14].…”
Section: Introductionmentioning
confidence: 99%
“…di-tert.butylphenol derivatives) but differentiation between individual species is not possible and quantification very complicated. Other methods presented only recently are the analysis of the solid samples by DESI [7], ASAP [8], DART [9], or SIMS [10]. In DESI (Desorption Electrospray Ionization) and DART (Direct Analysis in Realtime), the surface of a polymer is either put into an ESI spray or a helium stream, both resulting in the ionization of the volatile components of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many researches have successfully demonstrated the ability of DART for qualitative and quantitative analysis. Analysis of solids or liquids, including illegal additives [3], Chinese herbal preparations [4], human blood sera [5], peptides [6], oligosaccharides [7], synthetic organic molecules [8], organometallics [9], toxins [10], polymers [11], cosmetics [12], fungicides on wheat [13], counterfeit drugs [14], explosives on clothes or shoes [15,16], biological matrices [17], and environmental samples after stir bar sorptive extraction [18] have shown that the DART is a versatile method for rapid detection of analytes. These chemicals have been detected on surfaces including concrete, asphalt, human skin, currency, paper stock, vegetables, fruit, and even clothing.…”
mentioning
confidence: 99%